Solving Mathematics Problems Through Reflective Learning for High School Students - Hafiza Yusni; Irvan Irvan; Zulfi Amri (JMEA : Journal of Mathematics Education and Application, 2022)
This research is a quasi-experimental study because the treatment was tested and measured its effect on groups of samples. The experimental design used in the study was the design of a non-equivalent pretest and posttest control group. The population in this study were all students of the Sei Rampah Exemplary Vocational School in class X consisting of 145 students, and a sample of 40 students was chosen randomly. To obtain data in this study used an instrument, namely a set of problem-solving tests with indicators (a) formulating the problem, (b) restating the problem in a form that can be resolved, (c) arranging hypotheses (temporarily) and strategies for solving it, (d ) carry out solving procedures, and (e) evaluate the settlement. The results of this study indicate that the problem-solving ability of male students is better than female students when viewed based on the posttest scores obtained by male students significantly different from female students. Another thing also shows that reflective learning is significantly better in improving students' mathematical problem-solving abilities than ordinary learning.